Ultra Performance Liquid Chromatography-Tandem Mass Spectrometry-Based Metabolomics Reveals Metabolic Alterations in the Mouse Cerebellum During Toxoplasma gondii Infection - Ma, Jun; He, Jun-Jun; Hou, Jun-Ling; Zhou, Chun-Xue; Elsheikha, Hany M.; Zhu, Xing-Quan (Frontiers in Microbiology, 2020)
Toxoplasma gondii is a protozoan parasite with a remarkable neurotropism. We recently showed that T. gondii infection can alter the global metabolism of the cerebral cortex of mice. However, the impact of T. gondii infection on the metabolism of the cerebellum remains unknown. Here we apply metabolomic profiling to discover metabolic changes associated with T. gondii infection of the mouse cerebellum using ultra performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). Multivariate statistics revealed differences in the metabolic profiles between the infected and control mouse groups and between the infected mouse groups as infection advanced. We also detected 10, 22, and 42 significantly altered metabolites (SAMs) in the infected cerebellum at 7, 14, and 21 days post infection (dpi), respectively. Four metabolites [tabersonine, arachidonic acid (AA), docosahexaenoic acid, and oleic acid] were identified as potential biomarker or responsive metabolites to T. gondii infection in the mouse cerebellum. Three of these metabolites (AA, docosahexaenoic acid, and oleic acid) play roles in the regulation of host behavior and immune response. Pathway analysis showed that T. gondii infection of the cerebellum involves reprogramming of amino acid and lipid metabolism. These results showcase temporal metabolomic changes during cerebellar infection by T. gondii in mice. The study provides new insight into the neuropathogenesis of T. gondii infection and reveals new metabolites and pathways that mediate the interplay between T. gondii and the mouse cerebellum.